Analysis of Communication Effectiveness in the Digital Era as a Communication Media for iGeneration (Gen Z) during the Recovery Period of the COVID-19 Pandemic: Descriptive Study of MIKOM USU 2022 - Juli Purnawati; Dewi Kurniawati (Universitas Airlangga, 2023)
ABSTRACT All sectors are feeling the impact of the Corona virus outbreak, such as education, the economy, tourism, and others. This has also shifted the direct interpersonal communication system to the digital (online) media communication system. With the COVID-19 virus, all universities in North Sumatra, both public and private, received an appeal from the government to implement PSBB (Large-Scale Social Restrictions) and carry out social distancing, where all employees, lecturers, and students of the University of North Sumatra are required to carry out their activities and daily operations at WFH (Work From Home) homes. However, during this recovery period, campus activities began to be carried out offline and also online, so the purpose of this study was to identify and analyze the effectiveness, constraints, and digital communication solutions during the pandemic (COVID-19) and recovery during the COVID-19 pandemic. , in the Master of Communication Science, University of North Sumatra. This research was conducted using a qualitative approach and a descriptive method. The research results show the effectiveness of digital communication during the COVID-19 pandemic and COVID-19 recovery. Â Keywords: efektivitas, komunikasi digital, Pandemi COVID-19 dan Pemulihan COVID-19 Analisis Efektivitas Komunikasi di Era Digital Sebagai Media Komunikasi Pada iGeneration (Gen Z) di Masa Pemulihan Pandemi COVID-19 (Studi Deskriptif MIKOM USU 2022) ABSTRAK Semua sektor merasakan dampak dari wabah virus Corona, seperti pendidikan, ekonomi, pariwisata, dan lain-lain. Hal ini juga telah menggeser sistem komunikasi interpersonal langsung ke sistem komunikasi media digital (online)(Ardiyanti, 2020). Dengan adanya virus COVID-19, seluruh perguruan tinggi di SUMUT baik negeri maupun swasta mendapat himbauan dari pemerintah untuk menerapkan PSBB (Pembatasan Sosial Berskala Besar) dan melakukan social distancing, dimana seluruh karyawan, dosen, dan mahasiswa Universitas Sumatera Utara diwajibkan untuk melaksanakan kegiatan pekerjaan dan operasional sehari-hari mereka di rumah WFH (Work From Home). Namun pada masa recovery ini, kegiatan kampus mulai dilakukan secara offline dan juga online, sehingga tujuan dari penelitian ini adalah untuk mengidentifikasi dan menganalisis efektifitas, kendala, dan solusi komunikasi digital pada masa pandemi COVID-19 dan pemulihan pada masa pandemi COVID-19, di Magister Ilmu Komunikasi, Universitas Sumatera Utara. Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif dan metode deskriptif. Hasil penelitian menunjukkan efektivitas komunikasi digital selama pandemi COVID-19 dan pemulihan COVID-19. Kata Kunci : efektivitas, komunikasi digital, Pandemi COVID-19 dan Pemulihan COVID-19 Â